2022
DOI: 10.3390/f13010106
|View full text |Cite
|
Sign up to set email alerts
|

Variation and Genetic Control of the Heartwood, Sapwood, Bark, Wood Color Parameter, and Physical and Mechanical Properties of Dipteryx panamensis in Costa Rica

Abstract: The Dipteryx genus has a natural distribution throughout several tropical countries in Latin America. This taxon has several tree species, all recognized for their high-density wood. The objective of this research was to study the variation and genetic control of several wood properties, including bark, sapwood, heartwood, green density (GD), specific gravity (SG), moisture content in green condition (MC-G), and mechanical properties, in a Dipteryx panamensis provenance/progeny test at 8 years old. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 28 publications
1
0
0
Order By: Relevance
“…Regarding the physical properties of wood, it is well known that specific weight is one of the most important in terms of quality (Moya, 2004). However, there are few studies that relate this parameter to the genetic origin of trees in broadleaf species (Rodríguez-Pérez et al, 2022). Studies in tropical species report that specific weight decreases with stem height (Pande & Singh, 2005;Rodríguez-Pérez et al, 2022;Weber & Sotelo-Montes, 2008)), a situation that differs from this study where it was observed that values increase with stem height (Figure 3g).…”
Section: Wood Properties and Variationscontrasting
confidence: 80%
See 3 more Smart Citations
“…Regarding the physical properties of wood, it is well known that specific weight is one of the most important in terms of quality (Moya, 2004). However, there are few studies that relate this parameter to the genetic origin of trees in broadleaf species (Rodríguez-Pérez et al, 2022). Studies in tropical species report that specific weight decreases with stem height (Pande & Singh, 2005;Rodríguez-Pérez et al, 2022;Weber & Sotelo-Montes, 2008)), a situation that differs from this study where it was observed that values increase with stem height (Figure 3g).…”
Section: Wood Properties and Variationscontrasting
confidence: 80%
“…Moya (2004) reported 50 to 70 % heartwood in 12-year-old trees, while in the present study, the percentage of heartwood remained between 40 and 50 % with early-aged clones (three years old). Thus, Moya and Tomazello (2007) demonstrated that cloned trees have a significant amount of heartwood at an early age and that, probably, at the end of the rotation, the percentage of heartwood is higher, since it increases with tree age (Rodríguez-Pérez et al, 2022).…”
Section: Wood Properties and Variationsmentioning
confidence: 98%
See 2 more Smart Citations
“…9A, in which it can be seen that the shear strengths decreased from 25.62 GPa to 23.74 GPa with decreasing fluffed bamboo veneer content. However, these shear strengths are significantly higher than those obtained for Dipteryx panamensis in Costa Rica (19.3-19.6 GPa) [23]. Encouragingly, the shear strengths of all LC samples evaluated in this experiment were close to or greater than twice that required for high-class outdoor use, as stated in GB/T 30364-2013 for "bamboo scrimber flooring" (≥12 MPa).…”
Section: Shear Strengthsupporting
confidence: 45%